Correlations between biomarkers of varying bioavailability and putative hydrocarbonoclastic bacteria in an Early-Eocene marlstone sedimentary record - Wang, Danlei; Coolen, Marco; Idiz, E.; Holman, Alex; Hopper, Peter; Cockell, C.S.; Grice, Kliti (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
We examined the possibility that, during short-term refrigerated storage, microbial communities continue to biodegrade individual lipid biomarkers in an intact core section of Early Eocene consolidated marlstone sediments from the hydrothermal system overlying the Chicxulub impact crater (Yucatán, Mexico). Amplicon sequencing of environmental 16S rRNA obtained from the core samples revealed a high relative abundance of amplicon sequence variants (ASVs) related to known hydrocarbon degraders, notably Halomonas and Marinobacter. Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt2) predicted that Marinobacter and a subset of less abundant bacteria (e.g., Alcanivorax) have the genomic potential to anaerobically degrade hydrocarbons via dissimilatory nitrate reduction to ammonia. The variability in the relative abundance of these taxa showed strong positive Pearson correlations (Pearson's r > 0.5) with quantitative changes in the most bioavailable non-sulfurized compounds, notably polycyclic aromatic hydrocarbons (PAHs) and isorenieratane. Moderate positive Pearson correlations (r values between ∼0.3 and ∼0.5) were observed between microbial taxa and compounds that have undergone early abiotic diagenetic sulfurization (e.g., hopanes, n-alkanes and steranes). These results suggest that non-sulfurized biomarkers may be subject to continued biodegradation in marine sedimentary rocks during short-term refrigerated storage.